2016
DOI: 10.1902/jop.2016.150632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunoinflammatory Evaluation of One‐Stage Full‐Mouth Ultrasonic Debridement as a Therapeutic Approach for Smokers With Generalized Aggressive Periodontitis: A Short‐Term Follow‐Up Study

Abstract: Considering the clinical and immunoinflammatory parameters evaluated in this short-term follow-up study, it can be concluded that OSFMUD can be used as an alternative treatment for smokers with GAgP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Another study reported that GCF concentrations of IL-6 and TNF-decreased from baseline to 6 months in nonsmokers as well as smokers. 30 Although similar trends were observed, the current study agreed only in part with the earlier investigations presumably because of individual differences or by the complex nature of GAgP and possible presence of disease subgroups. This might be explained by the transient post-treatment falls and increases observed, paticularly for TNF-.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Another study reported that GCF concentrations of IL-6 and TNF-decreased from baseline to 6 months in nonsmokers as well as smokers. 30 Although similar trends were observed, the current study agreed only in part with the earlier investigations presumably because of individual differences or by the complex nature of GAgP and possible presence of disease subgroups. This might be explained by the transient post-treatment falls and increases observed, paticularly for TNF-.…”
Section: Discussionsupporting
confidence: 79%
“…16 However, another study reported contradicting data as both non-smokers and smokers exhibited similarly significant reductions in PD and bleeding scores between baseline and 6 months after non-surgical periodontal treatment. 30 Accordingly, the present study indicated similar outcomes for CAL and BOP in the smoker and non-smoker groups. Hawthorne effect may have had a role in the similar clinical outcomes in smoker and non-smoker groups.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies did not find any differences in TNF‐α levels after quadrant SRP with and without amoxicillin plus metronidazole at both 3 (Machtei & Younis, ) and 6 months (de Lima Oliveira et al, ). However, some did find a significant reduction after quadrant SRP at 6 months (Duarte et al, ; De Genaro Modanese et al, ; Romano et al, ). In the current study, OSFMD with amoxicillin plus metronidazole failed to reduce TNF‐α levels in GCF samples at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, regulating TNF‐α levels may be important for controlling aberrant apoptosis in GAgP. In the literature, there have been contradictory results with regard to the effects of non‐surgical periodontal treatment on TNF‐α levels in the GCF of GAgP patients (Duarte et al, ; De Genaro Modanese et al, ; de Lima Oliveira et al, ; Machtei & Younis, ; Romano et al, ). Some studies did not find any differences in TNF‐α levels after quadrant SRP with and without amoxicillin plus metronidazole at both 3 (Machtei & Younis, ) and 6 months (de Lima Oliveira et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation